Interfacial tension measurements of lubricants with greater adhesion to metal surfaces (Research, Society and Development, 2024)
The initial aim of this research was to study the surface tension and viscosity of oils and oil blends in order to develop a study on the miscibility of these lubricants. When conducting the described tests, little variation was obtained, making such a study unfeasible. Under these conditions, it was decided to only invest in what would already be the second stage of the study: investigating the interaction of these oils and their blends with a specific metal surface, aiming to correlate the oil's wettability on the surface with its lubrication efficiency. For this purpose, two oils and three of their blends were used, totaling five samples. As a final result, the greatest wettability was obtained on an aluminum surface for the 50-50 blend, indicating that it had a greater interaction with the metal surface and, theoretically, a higher lubrication efficiency. The mentioned efficiency would be higher as long as the other components of this blend did not present a very large incompatibility. Obviously, the chemical analysis required to address this concern was left as a suggestion for future research.